Contribution of Emotional Maturity with Behavioral Tendencies of Self-Injury In Adolescents - Rahardjo, Thalia Angelica; Kusumiati, Ratriana Yuli Endang (Program Studi Psikologi, Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Mulawarman, 2023)
Self-injury as the realization of self-harm is an act of self-harm that is carried out to overcome shocks and mental or emotional pain that is carried out whether intentional or not. Based on previous research sources and journals, it is known that emotional maturity is one of the predictors of the emergence of self-injury behavior tendencies, although there are still other external factors. Specifically, this study focused on the relationship of emotional maturity with the tendency of self-injury behavior in adolescents with the subjects of grade 12 SMA N students in Temanggung as many as 177 respondents. This research is in the form of quantitative research with information in the form of statistical data. Based on the results and analysis of the Spearman-Rho Product-Moment correlation that has been carried out, it is known that the correlation coefficient between the variable X (Emotional Maturity) and the variable Y (Self-Injury) is 0.045 with a Sig. value of 0.278 indicates that there is no correlation of emotional maturity with a tendency to self-injury behavior in adolescents. Furthermore, the value of the contribution of emotional maturity contributed to variable Y, namely self-injury of 4.5% based on the calculation of the correlation coefficient of 0.045 multiplied by 100% and obtained an effective contribution result of 4.5 for variable X to Y. The amount of emotional maturity contribution to the emergence of self-injury behavior tendencies was 4.5% while the rest was influenced by other factors outside of emotional maturity that could trigger the emergence of tendencies self-injury behavior in adolescents. It is hoped that with this research, there will be a lot of knowledge about that emotional maturity only contributes to self-injury behavior.Self-injury sebagai realisasi self-harm adalah sebuah tindakan melukai diri sendiri yang dilakukan guna menanggulangi guncangan serta rasa sakit mental atau emosional yang dilakukan baik disengaja ataupun tidak. Berdasarkan sumber penelitian dan jurnal terdahulu, diketahui bahwa kematangan emosi menjadi salah satu prediktor munculnya kecenderungan perilaku self-injury, meskipun masih terdapat faktor eksternal lainnya. Secara spesifik penelitian ini berfokus pada hubungan kematangan emosi dengan kecenderungan perilaku self-injury pada remaja dengan subjek siswa kelas 12 SMA N di Temanggung sebanyak 177 responden. Penelitian ini berbentuk penelitian kuantitatif dengan informasi berupa data statistik. Berdasarkan hasil dan analisis korelasi Product-Moment Spearman-Rho yang telah dilakukan, diketahui bahwa koefisien korelasi antara variabel X (Kematangan Emosi) dengan variabel Y (Self-Injury) adalah 0.045 dengan nilai Sig. 0.278 mengindikasikan tidak terdapat kolerasi kematangan emosi dengan kecenderungan perilaku self-injury pada remaja. Selanjutnya pada nilai kontribusi kematangan emosi memberikan sumbangan terhadap variabel Y yaitu self-injury sebesar 4.5% berdasarkan hasil perhitungan koefisien korelasi sebesar 0.045 dikalikan 100% dan memperoleh hasil sumbangan efektif sebesar 4.5 untuk variabel X terhadap Y. Besarnya sumbangan kematangan emosi terhadap munculnya kecenderungan perilaku self-injury sebesar 4.5% sedangkan selebihnya dipengaruhi oleh faktor lain diluar kematangan emosi yang bisa memicu munculnya kecenderungan perilaku self-injury pada remaja. Diharapkan dengan adanya penelitian ini banyak menyumbangkan pengetahuan mengenai bahwa kematangan emosi hanyalah sebagian kecil memberikan kontribusi terhadap perilaku self-injury.